EFEKTIVITAS MODEL OPEN INQUIRY TERHADAP KETERAMPILAN PROSES SAINS PADA MATERI EKOSISTEM - Eva Yuliana (Jurnal Inovasi Pendidikan dan Sains, 2020)
The purpose of this study was to determine the effectiveness of open inquiry models on science process skills in ecosystem material at MAN 1 Indramayu. The type of research is quantitative research, the design that used in this study is Quasi Experimental that use parametric statistics. The population in this study was all students of class X MAN 1 Indramayu which amounted to 185 students. They were in both class X MIA 1 totaling 25 students and X MIA 2 totaling 20 students with cluster random sampling technique. The instruments that used were five item description questions. Based on the results of processing and data analysis of science process skills obtained the results of hypothesis testing as follows: thitung = 6.0215 and ttable = 1.671. Because tcount>ttabel, it could be conclude that Ho was rejected, meaning that the open inquiry model effective students' science process skills in the ecosystem material